Worth of Celebrity Attributes on Purchasing Behaviour of Assurance Service in Sri Lanka: Mediating Effect of Source Credibility - K. M. V. Sachitra; A. K. G. Poornima (Archives of Current Research International, 2020)
Purpose: Celebrity endorsement has been investigated in prior studies regarding various behavioural and cognitive aspects about consumer purchasing behaviour, it is not clear whether principles findings in the general celebrity literature can be directly applied to the service context. This study examines the effects of different attributes associated with celebrities on purchasing behaviour of life insurance policy in Sri Lanka. Design: The study used a deductive approach and quantitative research design. Data were collected from 150 life insurance policy holders who representing four insurance companies in Sri Lanka. A self-administrated structured questionnaire was used to collect data. The step-wise multiple regression and regression-based path analysis were employed to test the hypotheses. Findings: The study finds that celebrity attractiveness, trustworthiness and expertise have significant influence over purchasing behaviour and however the influence is not strong. Further, celebrity trustworthiness has a significant mediating effect on the relationship between celebrity expertise and buying behaviour. Originality: Despite the role of celebrity attributes in influencing the buying behaviour of tangible products, limited studies have been conducted specifically on intangible products and also, the literature is not clear whether principle findings in the general celebrity can be directly applied to the intangible product or service context. This study has addressed that empirical gap.